Combinatorial Action of MicroRNAs let-7 and miR-34 Effectively Synergizes with Erlotinib to Suppress Non-small Cell Lung Cancer Cell Proliferation - Stahlhut, Carlos (Cell Cycle, 2015)
Lung cancer represents the leading cause of cancer-related deaths in men and women worldwide. Targeted therapeutics, including the epidermal growth factor receptor (EGFR) inhibitor erlotinib, have recently emerged as clinical alternatives for the treatment of non-small cell lung cancer (NSCLC). However, the development of therapeutic resistance is a major challenge, resulting in low 5-year survival rates. Due to their ability to act as tumor suppressors, microRNAs (miRNAs) are attractive candidates as adjuvant therapeutics for the treatment of NSCLC. In this study, we examine the ability of 2 tumor suppressor miRNAs, let-7b and miR-34a to sensitize KRAS;TP53 mutant non-small cell lung cancer cells to the action of erlotinib. Treatment with these miRNAs, individually or in combination, resulted in synergistic potentiation of the anti-proliferative effects of erlotinib. This effect was observed over a wide range of miRNA and erlotinib interactions, suggesting that let-7b and miR-34a target oncogenic pathways beyond those inhibited by EGFR. Combinatorial treatment with let-7b and miR-34a resulted in the strongest synergy with erlotinib, indicating that these miRNAs can effectively target multiple cellular pathways involved in cancer cell proliferation and resistance to erlotinib. Together, our findings indicate that NSCLC cells can be effectively sensitized to erlotinib by supplementation with tumor suppressor miRNAs, and suggest that the use of combinations of miRNAs as adjuvant therapeutics for the treatment of lung cancer is a viable clinical strategy.